Robotic or laparoscopic approach for hysterectomy: Comparison of operative outcomes and cost - Karakaş, Sema; Demirayak, Gökhan; Erdoğan, Şakir Volkan; Erdoğan, Aliye; Önder, Ayşe Büşra; Özdemir, İsa Aykut; Comba, Cihan; Süzen Çaypınar, Sema; Ekin, Murat; Yaşar, Levent; Afşar, Selim (Cukurova University, 2021)
Purpose: The present study aimed to compare surgical outcomes and cost analysis of robotic-assisted surgery (RAS) and conventional laparoscopic surgery (CLS) hysterectomy procedures. Materials and Methods: The patients who underwent total robotic hysterectomy or total conventional laparoscopic hysterectomy with or without bilateral salpingo-oophorectomy due to benign gynecological disorders such as uterine fibroid, abnormal uterine bleeding, endometrial hyperplasia, adenomyosis, persistent ovarian cysts, chronic pelvic pain were retrospectively evaluated. Results: A total of 80 women underwent RAS or CLS hysterectomy during the study period. The mean total operative time was 187 +/- 10 min. in RAS and 133 +/- 24 min. in CLS groups, respectively. The mean total cost of the RAS hysterectomy group was 17.710 TL, and CLS hysterectomy group was 7000 TL. Conclusion: Both CLS and RAS hysterectomies for benign gynecological indications are safe surgical procedures with negligible complication rates. RAS is a more expensive procedure compared to CLS.

Amaç: Bu çalışma, robotik yardımlı cerrahi (RAC) ve geleneksel laparoskopik cerrahi (GLC) histerektomi prosedürlerinin cerrahi sonuçlarını ve maliyet analizini karşılaştırmayı amaçlamaktadır. Gereç ve Yöntem: Uterin fibroid, anormal uterin kanama, endometrial hiperplazi, adenomiyozis, persiste eden over kistleri, kronik pelvik ağrı gibi benign jinekolojik bozukluklar nedeniyle bilateral salpingo-ooferektomi ile birlikte veya salpingo-ooferektomi olmaksızın total robotik histerektomi veya total konvansiyonel laparoskopik histerektomi uygulanan hastalar geriye dönük olarak değerlendirildi. Bulgular: Çalışma dönemi sırasında toplam 80 kadına RAC veya GLC histerektomi yapıldı. Ortalama toplam ameliyat süresi RAC ve GLC gruplarında sırasıyla 187 ± 10 dk. ve 133 ± 24 dk. idi . RAC histerektomi grubunun ortalama toplam maliyeti 17.710 TL ve GLC histerektomi grubunun 7000 TL idi. Sonuç: İyi huylu jinekolojik endikasyonlar için hem GLC hem de RAC histerektomiler ihmal edilebilir komplikasyon oranları ile güvenli cerrahi prosedürlerdir. Maliyetlerle ilgili olarak, RAC, GLC 'ye göre daha pahalı bir prosedürdür.
Histerektomide robotik veya laparoskopik yaklaşım: Operatif sonuçlar ve maliyet karşılaştırılması
Keywords: Hysterectomy; Gynecology; Robot-Enhanced Surgery; Laparoscopy; Histerektomi; Jinekoloji; Robot Destekli Cerrahi; Laparoskopi